The The Influence of the POGIL (Process Oriented Guided Inquiry Learning) Learning Model Assisted by Mind Mapping Media on Students' Critical Thinking Ability - Alhaj, Yusri; Sukardi; Nursaptini; Masyhuri (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2024)
This research aims to determine whether there is an influence of the POGIL (Process Oriented Guided Inquiry Learning) learning model assisted by mind mapping media on students' critical thinking abilities. This research uses a quasi-experimental quantitative approach with a posttest nonequivalent control group design. The research sample was taken using a random sampling technique after class matching was carried out. The instrument in this research is in the form of multiple choices questions which meet the instrument quality requirements. The data analysis in this study used descriptive statistics and two independent sample tests. The results of the study obtained a t value of4,725with probability 0.000<0.050. The results of the research show that there is an influence of the POGIL (Process Oriented Guided Inquiry Learning) learning model assisted by mind mapping media on students' critical thinking abilities. This increase in critical thinking skills can be attributed to innovation in the application of mind mapping media which is still rarely used.